Deslocamentos e mortalidade de peixes nos rios Grande e Paranaíba, MG - Alejandro Giraldo Pérez (2014)
In Brazil, information about downstream migration of fishes is scarce. There are no one Fish Passage Mechanisms (FPM) in the country designed specifically to allow downstream movements of fishes. Therefore, fishes going to lower portions of dammed rivers should transit through FPM built without this purpose, by turbines or by spillways, with survival rates not determined yet. Aiming to enhance this knowledge, I tagged 36 mandis (Pimelodus maculatus) with radio tags and tracked them since February of 2012 to September of 2013. I manually transpose mandis from Igarapava Fish Ladder (IFL), were I captured them, to Jaguara reservoir, where I released them. Until the end of this study, no one pass through Jaguara dam (via turbines or spillways), although three of them were within 100 m of it. Likewise, there were not mandis at the free river stretch imediatelly downstream of Estreito dam, located upstream of Jaguara reservoir. After short movements (< 14,5 km), mandis were predominately sedentary, remaining into the main channel of the Jaguara reservoir. Due to radiotelemetry limitations at depth bigger than 15 m, I had difficulties to localize mandis probably positioned at these depths. It is very important to execute studies aiming to establish which variables are influencing mandis to avoid passing through Jaguara dam.